Tanggung Jawab Negara Terhadap Pelanggaran Hak Asasi Manusia Di Belarusia Ditinjau Dari Hukum Internasional - Billy Diego Arli Papilaya; Johanis Steny Franco Peilouw; Richard Marsilio Waas (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Human rights violations that occurred in Belarus between the Belarusian Police and the demonstrators were an act that violated the provisions of the applicable laws and regulations. Purposes of the Research: This writing aims to examine and analyze how the regulation of state responsibility according to international law and the form of state responsibility for human rights violations in Belarus is arranged.Methods of the Research: The research method in this paper uses a normative juridical research type. The research approach used is a statutory approach, a conceptual approach and a case approach. The procedure for collecting legal materials uses primary legal materials and secondary legal materials through books, articles, journals and the writings of legal experts, as well as legal materials analysis techniques in this study using qualitative analysis techniques.Results of the Research: The results obtained are to explain that the state's responsibility for human rights violations in Belarus is a guarantee in upholding human rights, because the human rights violations committed by the Belarusian Police against the demonstrators are the responsibility of the state, where in upholding, protecting, fulfilling, respecting, and the responsibility of the state in promoting human rights in accordance with applicable regulations.